Star Wars : Darth Maul - Bunn, Cullen; Eliopoulos, Chris, 1983- (Star Wars, 2017)
Raised on hate, fear and anger...steeped in the ways of darkness...and trained to kill! Darth Maul's time as apprentice to Darth Sidious has long been cloaked in shadows - now at last his tale of revenge is revealed! It's a story of rage unleashed as Darth Maul prepares for his first encounter with the hated Jedi. But when a Jedi Padawan is captured by sinister forces, why is Maul so determined to fi nd her? And what role will a band of bounty hunters, including Cad Bane and Aurra Sing, play? Get to know the galaxy's deadliest Zabrak like never before!